A high-molecular carbon nanotube composite conductive film and a preparation method thereof

CN122991723APending Publication Date: 2026-10-27ZHONGSHAN ZHONGYUAN NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611385824.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-08
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,碳纳米管在聚合物基体中易发生团聚,且碳纳米管表面惰性导致其与高分子基体之间缺乏有效的化学结合,主要依赖物理填充和包覆作用

Benefits of technology

(1)本发明通过“酸化处理-硅烷偶联剂接枝”两步表面修饰策略在碳纳米管(CNT)表面构建反应性官能团,再采用梯度溶剂挥发诱导原位交联工艺,使高分子链段与碳纳米管表面的氨基发生梯度交联反应,形成具有梯度结构的界面相。本发明实现了碳纳米管与高分子基体之间的化学键合,有效克服了超薄膜中因热膨胀系数不匹配导致的微裂纹和附着力差的问题,具有工艺简化和规模化成本低的特点。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to a kind of polymer carbon nanotube composite conductive film and its preparation method, belong to the technical field of carbon nanotube composite film.The film includes substrate and composite conductive coating formed on the surface of the substrate;The composite conductive coating includes functional group modified carbon nanotube and polymer film-forming matrix;The surface of the functional group modified carbon nanotube is bonded by forming chemical crosslinking between reactive functional group and polymer film-forming matrix;The composite conductive coating has crosslinking density gradient distribution structure in thickness direction.By surface modification strategy, reactive functional group is constructed on the surface of carbon nanotube, then gradient solvent evaporation induced in-situ crosslinking process is used, so that polymer chain segment and amino on the surface of carbon nanotube occur gradient crosslinking reaction, form interface phase with gradient structure, effectively overcome the problem of microcrack and poor adhesion caused by mismatching of thermal expansion coefficient in ultrathin film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of carbon nanotube composite films, and more specifically, relates to a polymeric carbon nanotube composite conductive film and its preparation method. Background Technology

[0002] Conductive thin films are widely used in displays, touch screens, solar cells, organic light-emitting devices, thin-film transistors, and electromagnetic shielding. Currently, the mainstream conductive thin film material is indium tin oxide (ITO), but ITO suffers from drawbacks such as scarce indium resources, complex production processes, and high manufacturing costs. Carbon nanotubes (CNTs), due to their excellent optical, electrical, and mechanical properties, are considered one of the most promising materials to replace ITO in the preparation of conductive thin films.

[0003] Currently, the main methods for preparing carbon nanotube conductive films include vacuum filtration, inkjet printing, spin coating, spray coating, and dip coating. However, carbon nanotubes are prone to aggregation in polymer matrices, and the inertness of the carbon nanotube surface leads to a lack of effective chemical bonding between them and the polymer matrix, relying mainly on physical filling and coating. This physical interface bonding method causes two prominent problems in ultrathin films (thickness ≤100nm): first, the mismatch in the coefficient of thermal expansion (CTE) between carbon nanotubes and the polymer matrix generates internal stress during thermal cycling, leading to the initiation and propagation of microcracks on the film surface; second, the interfacial bonding strength provided by physical coating is limited, and the film is easily peeled off from the substrate surface under repeated bending or thermal stress, resulting in poor adhesion. These defects severely limit the reliability and service life of carbon nanotube composite conductive films in fields such as flexible electronic devices.

[0004] To address the aggregation problem of carbon nanotubes, some studies have proposed strategies such as surface acidification modification and silane coupling agent modification. However, current technologies still primarily rely on physical mixing and layer-by-layer assembly, and the interfacial bonding between carbon nanotubes and the polymer matrix remains mainly physical. This fails to fundamentally solve the problems of microcrack generation and poor adhesion in ultrathin films, and also lacks a framework for subsequent structural design after carbon nanotube modification to regulate interfacial stress distribution. Furthermore, the reported chemical modification processes for carbon nanotube surfaces are complex and costly, limiting their widespread adoption in industrial production. Summary of the Invention

[0005] The purpose of this invention is to provide a polymer carbon nanotube composite conductive film and its preparation method, which enhances the interfacial bonding between carbon nanotubes and polymer matrix through chemical bonding, and has the characteristics of excellent adhesion.

[0006] The objective of this invention can be achieved through the following technical solutions: A polymeric carbon nanotube composite conductive film, the film comprising a substrate and a composite conductive coating formed on the surface of the substrate; The composite conductive coating comprises functionalized carbon nanotubes and a polymer film-forming matrix. The functionalized carbon nanotube surface forms chemical cross-linking bonds with the polymer film-forming matrix through reactive functional groups; The composite conductive coating consists of at least two sublayers with different crosslinking densities. There is no clear interface between the sublayers, and the crosslinking density is continuously and gradually distributed along the thickness direction, forming a crosslinking density gradient distribution structure. The sublayers are formed by sequentially coating and in-situ crosslinking at least two gradient prepolymer solutions with different carbon nanotube / polymer ratios.

[0007] In this invention, the formation mechanism of the crosslinking density gradient distribution structure is as follows: During the gradient coating process, the carbon nanotube concentration is highest in the bottom layer (near the substrate interface), and the solvent evaporates first. The movement of polyvinyl alcohol (PVA) segments is restricted, and the crosslinking reaction terminates earlier, forming a relatively loose crosslinking network. Conversely, the carbon nanotube concentration is lowest in the surface layer (near the air interface), the solvent evaporates more slowly, and the PVA segments retain their mobility for a longer period, allowing the crosslinking reaction to proceed more fully. Simultaneously, the gradient heating process further amplifies this difference in reaction kinetics from the inside out, thus forming a gradient distribution of crosslinking density that gradually changes from the substrate interface to the air surface in the thickness direction. Specifically, during the gradient heating stage (25–85°C), the hydrolysis condensation and hydrogen bonding of the silane coupling agent mainly occur, while the dehydration condensation crosslinking of amino and hydroxyl groups is mainly completed during the subsequent hot pressing treatment (80–120°C), thereby ensuring the formation and fixation of the gradient structure.

[0008] Preferably, the functionalized carbon nanotubes are multi-walled or single-walled carbon nanotubes grafted with aminosilane coupling agents after acidification treatment, and the grafting rate is 4-12% based on the mass of the carbon nanotubes. The polymer film-forming matrix is ​​polyvinyl alcohol; The chemical cross-linking bond is a chemical bond between amino and hydroxyl groups; The substrate is selected from one of PET film, glass, flexible polymer film, metal foil or ceramic substrate.

[0009] More preferably, the degree of polymerization of the polyvinyl alcohol is 500-2600, more preferably 1500-1800; and the degree of hydrolysis is 88%-99%, more preferably 98%-99%.

[0010] The preparation method of the polymer carbon nanotube composite conductive film described above includes the following steps: Step (1): Disperse carbon nanotubes in a mixed acid for oxidation treatment to obtain acid-modified carbon nanotubes; Step (2): Disperse the acidified modified carbon nanotubes obtained in step (1) in a solvent system, add an aminosilane coupling agent to carry out a grafting reaction, and obtain amino-functionalized carbon nanotubes (CNT-NH2). Step (3): Mix the amino-functionalized carbon nanotubes obtained in step (2) with the polymer film-forming matrix precursor solution to form at least two gradient prepolymer solutions with different carbon nanotube / polymer ratios. Step (4): The different gradient prepolymer solutions prepared in step (3) are sequentially coated on the substrate surface in proportion, and then the gradient temperature is increased to volatilize, so that the amino-functionalized carbon nanotubes and the polymer film-forming matrix undergo in-situ crosslinking reaction, forming a distribution structure in the coating thickness direction where the crosslinking density gradually changes from the inside to the outside, and a composite coating with a gradient crosslinking structure is obtained. Step (5): The composite coating obtained in step (4) is subjected to hot pressing to obtain a polymer carbon nanotube composite conductive film.

[0011] Preferably, in step (1), the carbon nanotube is a multi-walled carbon nanotube with a length of 0.5 to 10 μm and a diameter of 5 to 20 nm; The mass-to-volume ratio of the carbon nanotubes to the mixed acid is 1:10 to 1:50 (g / mL). The mixed acid is obtained by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of (2.5~3.5):1. The oxidation treatment is carried out at a temperature of 40–60°C for 3–8 hours.

[0012] More preferably, the oxidation treatment is carried out at a temperature of 50°C for 6 hours.

[0013] Preferably, in step (2), the aminosilane coupling agent is KH-540 or KH-550; The aminosilane coupling agent has a mass fraction of 2-8 wt% in the solvent system. The solvent system is an ethanol-water mixed solvent, with a volume ratio of ethanol to water of 85:15 to 95:5. The mass-to-volume ratio of the acidified carbon nanotubes to the solvent system is 1:20 to 1:100 (g / mL). The grafting reaction was carried out at a pH of 4.5–5.5, a reaction temperature of 60–80°C, and a reaction time of 2–6 hours.

[0014] More preferably, the aminosilane coupling agent has a mass fraction of 4-6 wt% in the solvent system.

[0015] Preferably, in step (3), the polymer film-forming matrix precursor solution is an aqueous solution of polyvinyl alcohol, wherein the mass fraction of polyvinyl alcohol is 0.5-5 wt%. The at least two gradient prepolymer solutions with different proportions are a first gradient prepolymer solution, a second gradient prepolymer solution, and a third gradient prepolymer solution; The mass ratios of carbon nanotubes to polyvinyl alcohol in the first gradient prepolymer solution, the second gradient prepolymer solution, and the third gradient prepolymer solution are 15:85–25:75, 8:92–12:88, and 0:100–5:95, respectively.

[0016] Preferably, in step (3), the gradient prepolymer solution further contains a crosslinking agent, which is selected from at least one of glutaraldehyde and dicyclohexylcarbodiimide, and the amount of the crosslinking agent is 0.1 to 2% of the mass of polyvinyl alcohol.

[0017] The addition of crosslinking agent has two main effects: firstly, it crosslinks with polyvinyl alcohol, enhancing the network strength of the polyvinyl alcohol matrix itself; secondly, it may further enhance the interfacial bonding between carbon nanotubes and polyvinyl alcohol by undergoing a Schiff base reaction with carbon nanotubes.

[0018] Preferably, in step (4), the proportional sequential coating means: coating in the order of the first gradient prepolymer solution, the second gradient prepolymer solution, and the third gradient prepolymer solution, and the coating method is selected from one of spin coating, spraying, scraping or slot coating. The wet film thickness of each gradient prepolymer solution is independently 10–100 μm. The gradient temperature volatilization refers to a stepwise temperature increase from 25-35℃ to 45-55℃ and then to 75-85℃ under RH conditions of 40-60%, with a holding time of 3-10 minutes after each temperature increase.

[0019] The in-situ crosslinking reaction includes: during the gradient heating process, the silanol groups generated by the hydrolysis of the ethoxy group of the silane coupling agent form Si-OC bonds with the hydroxyl groups on the surface of the carbon nanotubes, while the amino group and the hydroxyl group of the polyvinyl alcohol side chain are bonded by hydrogen bonds; in the subsequent hot pressing treatment, the amino group and the hydroxyl group undergo a dehydration condensation crosslinking reaction to form a covalent bond network.

[0020] Preferably, in step (5), the hot pressing conditions are: temperature 80-120℃, pressure 5-15MPa, and processing time 2-8 minutes; the thickness of the polymer carbon nanotube composite conductive film obtained in step (5) is 50-150nm, preferably 80-100nm.

[0021] Applications of the aforementioned polymeric carbon nanotube composite conductive films or polymeric carbon nanotube composite conductive films prepared according to the aforementioned preparation methods in antistatic packaging films, electromagnetic shielding films, flexible touch screens, electrochromic devices, organic light-emitting devices, solar cells, or heating films.

[0022] Furthermore, the polymeric carbon nanotube composite conductive film of the present invention can be widely used in high-end new materials fields such as antistatic packaging, electromagnetic shielding, and flexible displays.

[0023] The beneficial effects of this invention are: (1) This invention constructs reactive functional groups on the surface of carbon nanotubes (CNTs) through a two-step surface modification strategy of "acidification treatment - silane coupling agent grafting". Then, a gradient solvent evaporation-induced in-situ crosslinking process is used to induce a gradient crosslinking reaction between polymer segments and amino groups on the surface of carbon nanotubes, forming an interface phase with a gradient structure. This invention achieves chemical bonding between carbon nanotubes and the polymer matrix, effectively overcoming the problems of microcracks and poor adhesion caused by the mismatch of thermal expansion coefficients in ultrathin films. It has the advantages of simplified process and low cost for large-scale production.

[0024] (2) This invention creatively simplifies the surface modification of carbon nanotubes into two steps: “acidification treatment-silane coupling agent grafting”. It omits the NaBH4 reduction step and harsh oxidation conditions in the traditional process. While maintaining the integrity of the carbon nanotube conductive network, it achieves amino functionalization of the carbon nanotube surface. The grafting rate can reach 5-10% (mass percentage based on the carbon nanotube mass). While ensuring the effective dispersion of carbon nanotubes in the matrix, it significantly simplifies the process and reduces production costs by omitting the reduction treatment step. At the same time, combined with the gradient structure design, it achieves a comprehensive balance of conductivity, adhesion and resistance to thermal cycling cracking, making it more suitable for large-scale industrial production.

[0025] (3) This invention constructs an interfacial phase structure in which the carbon nanotube concentration decreases gradually from the substrate interface to the air interface and the crosslinking density gradually changes from the inside to the outside through gradient prepolymer solution design and gradient solvent evaporation-induced in-situ crosslinking process. This gradient structure creates a gradual transition zone of "interfacial anchoring - network crosslinking - flexible buffer" inside the film, effectively releasing the internal stress caused by the mismatch of thermal expansion coefficients between carbon nanotubes and polymer matrix, reducing the resistivity change rate of the film after high and low temperature thermal cycling, and preventing the generation of microcracks on the film surface.

[0026] (4) The present invention establishes a stable chemical bonding interface between carbon nanotubes and polymer matrix through Si-OC covalent bonds and amino-hydroxyl condensation crosslinking formed by silane coupling agent grafting, which replaces the traditional interface bonding method mainly based on physical filling and physical adsorption, thereby improving the adhesion between the film and the substrate and greatly enhancing the service reliability of the film. Detailed Implementation

[0027] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described below with reference to specific embodiments, but the scope of protection of this invention is not limited thereto. Experimental methods not specifically described in the embodiments are generally performed under conventional conditions or according to the manufacturer's recommendations. Unless otherwise specified, all reagents and materials used are commercially available.

[0028] Example 1 A polymeric carbon nanotube composite conductive film is prepared by the following method: (1) Acidification treatment of carbon nanotubes: 5g of GT-220 multi-walled carbon nanotubes (MWCNTs, tube diameter 5-15nm, tube length 1-5μm) provided by Shandong Dazhan Nanomaterials Co., Ltd. were dispersed in 150mL of concentrated H2SO4 / concentrated HNO3 mixed acid (volume ratio 3:1) and stirred in an oil bath at 50℃ for 6 hours. After the reaction was completed, the mixture was cooled to room temperature, diluted with deionized water, filtered and washed until the pH of the filtrate was 7, and the product was placed in a vacuum drying oven and dried at 60℃ for 12 hours to obtain acid-modified MWCNTs.

[0029] (2) Grafting with silane coupling agent: Take 4g of the acidified modified MWCNTs obtained in step (1), sonicate them in 200mL of ethanol / water mixed solvent (volume ratio 90:10), adjust the pH of the solution to 5.0 with dilute acetic acid, add KH-550 (mass fraction 5wt%), and reflux the reaction at 70℃ under nitrogen protection for 4 hours. After the reaction is completed, centrifuge the mixture, wash it three times with anhydrous ethanol, and dry it under vacuum at 60℃ for 12 hours to obtain amino-functionalized MWCNTs.

[0030] (3) Preparation of gradient prepolymer solutions: Polyvinyl alcohol (PVA, degree of polymerization 1700, degree of hydrolysis 99%) was dissolved in deionized water to prepare a 2wt% PVA aqueous solution. The amino-functionalized MWCNTs obtained in step (2) were mixed with the PVA aqueous solution at different mass ratios and ultrasonically dispersed to prepare three gradient prepolymer solutions: First gradient solution: CNT:PVA = 20:80 (CNT content 0.5wt%) Second gradient solution: CNT:PVA = 10:90 (CNT content 0.22wt%) Third gradient solution: CNT:PVA = 2:98 (CNT content approximately 0.04wt%) (4) Gradient coating and solvent evaporation-induced in-situ crosslinking: The PET film (125 μm thick) was ultrasonically cleaned sequentially with acetone, ethanol, and deionized water for 15 minutes, dried with nitrogen, and placed in a plasma processor for hydrophilic treatment (air atmosphere, power 100W, treatment time 5 minutes). The following coatings were then sequentially applied to the surface of the PET film using spin coating: First gradient solution (1000 rpm, spin coating for 30 seconds, wet film thickness approximately 40 μm, dry film thickness approximately 30 nm). Second gradient solution (1200 rpm, spin coating for 30 seconds, wet film thickness approximately 35 μm, dry film thickness approximately 25 nm). Third gradient solution (1200 rpm, spin coating for 30 seconds, wet film thickness approximately 35 μm, dry film thickness approximately 25 nm).

[0031] The total thickness of the three-layer dry film is approximately 80 nm. After each spin-coating, the film is placed in a constant temperature chamber with a humidity of 50% RH for gradient temperature volatilization: 30℃ for 5 minutes → 50℃ for 5 minutes → 80℃ for 10 minutes. During this process, the silanol groups generated by the hydrolysis of ethoxy groups in KH-550 form Si-OC bonds with the hydroxyl groups on the surface of carbon nanotubes, while the amino groups are bonded to the hydroxyl groups of the polyvinyl alcohol side chains through hydrogen bonds.

[0032] The crosslinking density of the bottom layer in Example 1 was determined to be (1.2 ± 0.2) × 10⁻⁶. -3 mol / m 3 The intermediate layer is (2.5±0.3)×10 -3 mol / m 3 The surface layer is (4.8±0.4)×10 -3 mol / m 3 The ratio of the three is approximately 1:2.1:4.0, showing a clear gradient increasing trend.

[0033] (5) Hot-press densification treatment: The film obtained in step (4) is placed in a hot press and hot-pressed for 5 minutes at a temperature of 100℃ and a pressure of 8MPa. After natural cooling to room temperature, a polymeric carbon nanotube composite conductive film with a thickness of about 80-100nm is obtained. During the hot-pressing treatment, amino and hydroxyl groups undergo dehydration condensation crosslinking reaction to form a covalent bond network. At the same time, the CNT concentration decreases gradually from the PET interface to the air surface.

[0034] Example 2 Compared with Example 1, the difference in this example is that in step (3) of this example, glutaraldehyde, a crosslinking agent, is added to each gradient solution, with an addition amount of 0.8 wt% of the mass of polyvinyl alcohol. The remaining components, preparation steps and parameters are the same.

[0035] Example 3 Compared with Example 1, the difference in this example is that the gradient coating method in step (4) is changed from spin coating to slot coating. The first gradient solution → second gradient solution → third gradient solution are coated sequentially on the surface of the hydrophilic treated PET film. The thickness of each coating layer is controlled to be 25nm, 25nm, and 30nm, respectively, with a total thickness of about 80nm. The remaining components, preparation steps, and parameters are the same.

[0036] Comparative Example 1 This comparative example uses a three-step method of "acid oxidation + NaBH4 reduction + silane coupling" to modify the surface of MWCNTs. The specific steps are as follows: S1. The carbon nanotubes were acidified according to step (1) of Example 1, but the treatment time was extended to 8 hours. Then, the acidified MWCNTs were dispersed in deionized water, NaBH4 (0.8wt%) was added, and the mixture was stirred and reduced at 60°C for 5 hours. After taking it out, it was centrifuged and washed until neutral, and then silane coupling agent grafting was performed according to step (2) of Example 1.

[0037] S2. The modified MWCNTs and PVA aqueous solution (2wt%) were mixed at a mass ratio of CNT:PVA=10:90 and ultrasonically dispersed to obtain a single-component monolayer prepolymer solution.

[0038] S3. Using spin coating (1200 rpm, 30 seconds), the above-mentioned monolayer prepolymer solution is coated onto the surface of a PET film that has been treated with plasma hydrophilicity.

[0039] S4. Dry the coated film in an 80°C oven for 10 minutes.

[0040] S5. Perform hot pressing treatment according to step (5) of Example 1 to obtain the finished film. The thickness of the obtained film is about 90 nm.

[0041] Comparative Example 2 Compared to Comparative Example 1, this comparative example differs in that it omits step S1; that is, the carbon nanotubes undergo no surface modification, and the original MWCNTs are directly subjected to steps S2 to S5. The resulting film thickness is approximately 90 nm.

[0042] Comparative Example 3 Compared with Example 1, the difference of this comparative example is that the acidification step (1) is omitted in this comparative example, and the original MWCNTs are directly subjected to steps (2) to (5).

[0043] Comparative Example 4 Compared with Example 1, the difference of this comparative example is that step (2) silane coupling agent grafting step is omitted in this comparative example, that is, the MWCNTs after acid treatment in step (1) are directly subjected to steps (3) to (5).

[0044] Comparative Example 5 Compared with Example 1, the difference in this comparative example is that in step (3) of this comparative example, amino-functionalized MWCNTs and PVA aqueous solution (2.0wt%) are mixed at a single mass ratio of CNT:PVA=10:90 and ultrasonically dispersed evenly to prepare only one prepolymer solution; in step (4), the above single prepolymer solution is coated once by spin coating. Other steps are the same as in Example 1.

[0045] Comparative Example 6 Compared with Example 1, the difference of this comparative example is that in step (4) of this comparative example, the coated film is directly dried in an 80°C oven for 15 minutes (without the gradient temperature rise process of 30°C→50°C→80°C), and the other steps are the same as in Example 1.

[0046] Comparative Example 7 Compared with Example 1, the difference of this comparative example is that step (5) is omitted in this comparative example, that is, after step (4) is completed, no hot pressing is performed, and the film is obtained directly.

[0047] Performance testing methods: (1) Sheet resistance: The four-probe method was adopted. According to GB / T37152, an RTS-9 four-probe tester was used. The probe spacing was 1.0 mm, the probe pressure was 0.2 to 0.5 N, the test temperature was 23 ± 2 °C, and the relative humidity was 45 ± 5%. No less than 5 test points were randomly selected on the film surface, and each test point was measured 3 times and the average value was taken.

[0048] (2) Adhesion: The cross-cut test (100-square test) was used. Referring to GB / T9286, a 6×6 grid (25 effective squares) with a 1mm spacing was cut into the film surface using a cross-cutting device, with the cutting depth penetrating the coating to the PET substrate surface. The chips were brushed away along the diagonal of the squares with a soft brush. 3M 600 tape was applied to the cut area and rolled 5 times with a rubber roller. The tape was then quickly peeled off at a 60° angle within 60±5 seconds. The integrity of the coating within the squares was observed using a 10x magnifying glass, and the grade was determined according to the GB / T9286 grading standard (5B being the best, 1B the worst). Each sample was tested 3 times.

[0049] (3) Thermal cycling stability: Refer to GB / T2423.22, use a high and low temperature test chamber, and set the temperature range to -20°C. At 100°C, each temperature point was held for 30 minutes, with a heating / cooling rate of 10°C / min. Each cycle from -20°C to 100°C to -20°C was counted as one cycle, and a total of 100 cycles were performed. The sheet resistance was tested before and after the thermal cycle according to method (1), and the rate of change of resistance was calculated using the following formula: ΔR = |R1 - R0| / R0 × 100% (R0 is the initial sheet resistance, and R1 is the sheet resistance after the cycle). At the same time, the initiation and propagation of microcracks on the thin film surface were observed using an optical microscope, and the crack density, length, and distribution characteristics were recorded.

[0050] (4) Elongation at break: According to GB / T1040.3, the film is cut into dumbbell-shaped standard specimens and a universal tensile testing machine is used. The initial gauge length is 20 mm and the tensile rate is 10 mm / min. At least 5 specimens are tested for each group of samples.

[0051] (5) CNT dispersion stability: Using UV-Vis spectrophotometry (dynamic sedimentation method), referring to GB / T33818 and ISO / TS21356-1, the CNTs to be tested were dispersed in DMF at a concentration of 0.1 wt%, and ultrasonically dispersed for 30 minutes (power 200W, frequency 40kHz). The dispersed CNTs were then transferred to cuvettes and allowed to stand. The absorbance of the supernatant was measured at the characteristic absorption wavelength (approximately 500 nm) at specified time intervals (0h, 6h, 12h, 24h, 48h, 72h, 120h, 240h). Using the initial concentration as a reference (100%), the relative concentration was calculated using the following formula: Relative concentration = (A... t / A0)×100% (A0 is the initial absorbance, A t (Absorbance after standing for time t). The time required for the relative concentration to decrease to 80% of the initial concentration is recorded as a quantitative indicator of dispersion stability.

[0052] (6) Determination of crosslinking density: The equilibrium swelling method was adopted, referring to GB / T 3690 and ASTM D2765. The film sample was accurately weighed and then immersed in deionized water, swelling at 25℃ until equilibrium was reached (approximately 72 hours). After removal, the surface moisture was blotted dry with filter paper, and the mass after swelling was weighed. The sample was then placed in a vacuum oven and dried at 80℃ until constant weight, and the dry weight was weighed. The crosslinking density (ν) was calculated according to the Flory-Rehner equation. e Unit: mol / m 3Since each sublayer is relatively thin and difficult to separate individually, a method of preparing parallel monolayer film samples was used to indirectly estimate the crosslinking density of each sublayer. Three monolayer film samples (thickness controlled at approximately 25–30 nm) were prepared separately on a PET substrate according to the first, second, and third gradient carbon nanotube / polyvinyl alcohol ratios, under the same coating and hot-pressing conditions as in the examples. Their crosslinking densities were measured separately and used as approximate values ​​for the crosslinking densities of the bottom, middle, and top layers in the gradient film. At least five parallel samples were prepared for each ratio, and the average value was taken. The crosslinking density gradient was determined as follows: if the ratio of the maximum to the minimum value among the bottom, middle, and top layers was ≥2.0, it was considered to have a significant crosslinking density gradient; if the ratio was <1.5, it was considered to have no significant gradient.

[0053] The test results are shown in Tables 1 and 2.

[0054] Table 1

[0055] Table 2

[0056] Based on the test results in Table 1, it can be seen that Examples 1-3 significantly outperformed all comparative examples in key performance indicators such as sheet resistance, adhesion, and thermal cycling stability, achieving a comprehensive balance of high conductivity, high adhesion, and excellent crack resistance. Among them, Example 2 exhibited the best overall performance, indicating that the introduction of the crosslinking agent comprehensively improved the mechanical properties and thermal cycling stability of the film. The crosslinking density gradient data further confirmed that Examples 1-3 all possessed a clear gradient characteristic of increasing crosslinking density from the bottom layer to the surface layer. In contrast, the comparative examples, lacking gradient structure design or with insufficient crosslinking reaction, lacked this gradient characteristic, leading to stress concentration during thermal cycling, resulting in microcracks and decreased adhesion.

[0057] Regarding surface modification, Comparative Examples 3 and 4 were compared with Example 1. Comparative Example 3 exhibited high sheet resistance, low adhesion, a high rate of change in resistance after thermal cycling, and noticeable surface cracks. This indicates that without acidification treatment, the carbon nanotube surface lacked sufficient hydroxyl groups, significantly reducing the grafting efficiency of the silane coupling agent, resulting in insufficient amino functionalization and weakened subsequent chemical crosslinking effects. Comparative Example 4 showed relatively high sheet resistance, low adhesion, and a high rate of change in resistance after thermal cycling. This suggests that relying solely on the hydrogen bonding between the carboxyl groups introduced by acidification and the hydroxyl groups of polyvinyl alcohol provides limited interfacial bonding strength, failing to meet the reliability requirements of the ultrathin film under thermal cycling conditions.

[0058] While Comparative Example 1 exhibited the best carbon nanotube dispersion stability, its adhesion was only at the 2B level, and its thermal cycling resistance change rate was as high as 42±5%. This indicates that even with a more complex three-step surface modification of carbon nanotubes, the microcrack problem caused by thermal expansion coefficient mismatch in ultrafilms cannot be solved without a gradient structure design. This demonstrates that simply improving CNT dispersion cannot solve the interfacial failure problem of ultrafilms under thermal cycling conditions. This invention, through a gradient crosslinking structure design, achieves a significant improvement in adhesion and crack resistance while ensuring sufficient CNT dispersion, demonstrating a synergistic optimization effect on overall performance.

[0059] Regarding the gradient structure design, although Comparative Example 5 had the same surface modification of carbon nanotubes as Example 1, it exhibited a high rate of change in electrical resistance after thermal cycling, and obvious surface cracks appeared. This indicates that even if the carbon nanotubes underwent complete surface modification, without a gradient structure inside the film, it is still unable to effectively buffer the mismatch in thermal expansion coefficients between the carbon nanotubes and polyvinyl alcohol, resulting in noticeable microcracks after thermal cycling.

[0060] Regarding process conditions, Comparative Examples 6 and 7 were compared with Example 1. Comparative Example 6 showed a higher resistivity change rate after thermal cycling than Example 1, and slight surface cracks appeared. This indicates that gradient heating and evaporation help control the crosslinking reaction rate, allowing the crosslinking reaction to proceed in an orderly manner during solvent evaporation, forming a more uniform and complete gradient interface phase. Comparative Example 7 exhibited high sheet resistance, low adhesion, and a high resistivity change rate after thermal cycling. This demonstrates that hot-press densification not only eliminates micropores formed during coating and voids caused by residual solvent evaporation, but also promotes further reaction of incompletely crosslinked functional groups, enhancing interfacial bonding.

[0061] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A polymeric carbon nanotube composite conductive film, characterized in that, The thin film includes a substrate and a composite conductive coating formed on the surface of the substrate; The composite conductive coating comprises functionalized carbon nanotubes and a polymer film-forming matrix. The functionalized carbon nanotube surface forms chemical cross-linking bonds with the polymer film-forming matrix through reactive functional groups; The composite conductive coating consists of at least two sublayers with different crosslinking densities. There is no clear interface between the sublayers, and the crosslinking density is continuously and gradually distributed along the thickness direction, forming a crosslinking density gradient distribution structure. The sublayers are formed by sequentially coating and in-situ crosslinking at least two gradient prepolymer solutions with different carbon nanotube / polymer ratios.

2. The polymeric carbon nanotube composite conductive film according to claim 1, characterized in that, The functionalized carbon nanotubes are multi-walled or single-walled carbon nanotubes grafted with aminosilane coupling agents after acidification treatment, with a grafting rate of 4-12% based on the mass of the carbon nanotubes. The polymer film-forming matrix is ​​polyvinyl alcohol; The chemical cross-linking bond is a chemical bond between amino and hydroxyl groups; The substrate is selected from one of PET film, glass, flexible polymer film, metal foil or ceramic substrate.

3. A method for preparing a polymeric carbon nanotube composite conductive thin film as described in claim 1 or 2, characterized in that, The preparation method includes the following steps: Step (1): Disperse carbon nanotubes in a mixed acid for oxidation treatment to obtain acid-modified carbon nanotubes; Step (2): Disperse the acidified modified carbon nanotubes obtained in step (1) in a solvent system, add an aminosilane coupling agent to carry out a grafting reaction, and obtain amino-functionalized carbon nanotubes. Step (3): Mix the amino-functionalized carbon nanotubes obtained in step (2) with the polymer film-forming matrix precursor solution to form at least two gradient prepolymer solutions with different carbon nanotube / polymer ratios. Step (4): The different gradient prepolymer solutions prepared in step (3) are sequentially coated onto the substrate surface in proportion, and then the gradient temperature is increased to volatilize, so as to obtain a composite coating with a gradient crosslinking structure. Step (5): The composite coating obtained in step (4) is subjected to hot pressing to obtain a polymer carbon nanotube composite conductive film.

4. The preparation method according to claim 3, characterized in that, In step (1), the carbon nanotubes are multi-walled carbon nanotubes with a length of 0.5 to 10 μm and a diameter of 5 to 20 nm; The mass-to-volume ratio of the carbon nanotubes to the mixed acid is 1:10 to 1:50 (g / mL). The mixed acid is obtained by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of (2.5~3.5):

1. The oxidation treatment is carried out at a temperature of 40–60°C for 3–8 hours.

5. The preparation method according to claim 3, characterized in that, In step (2), the aminosilane coupling agent is KH-540 or KH-550; The aminosilane coupling agent has a mass fraction of 2-8 wt% in the solvent system. The solvent system is an ethanol-water mixed solvent, with a volume ratio of ethanol to water of 85:15 to 95:

5. The mass-to-volume ratio of the acidified carbon nanotubes to the solvent system is 1:20 to 1:100 (g / mL). The grafting reaction was carried out at a pH of 4.5–5.5, a reaction temperature of 60–80°C, and a reaction time of 2–6 hours.

6. The preparation method according to claim 3, characterized in that, The polymer film-forming matrix precursor solution is an aqueous solution of polyvinyl alcohol, wherein the mass fraction of polyvinyl alcohol is 0.5-5 wt%; the at least two gradient prepolymer solutions with different proportions are a first gradient prepolymer solution, a second gradient prepolymer solution, and a third gradient prepolymer solution; The mass ratios of carbon nanotubes to polyvinyl alcohol in the first gradient prepolymer solution, the second gradient prepolymer solution, and the third gradient prepolymer solution are 15:85–25:75, 8:92–12:88, and 0:100–5:95, respectively.

7. The preparation method according to claim 3, characterized in that, In step (3), the gradient prepolymer solution also contains a crosslinking agent, which is selected from at least one of glutaraldehyde and dicyclohexylcarbodiimide, and the amount of the crosslinking agent is 0.1 to 2% of the mass of polyvinyl alcohol.

8. The preparation method according to claim 3, characterized in that, In step (4), the proportional sequential coating means coating in the order of the first gradient prepolymer solution, the second gradient prepolymer solution, and the third gradient prepolymer solution, and the coating method is selected from one of spin coating, spraying, scraping or slot coating. The wet film thickness of each gradient prepolymer solution is independently 10–100 μm. The gradient temperature volatilization refers to a stepwise temperature increase from 25-35℃ to 45-55℃ and then to 75-85℃ under RH conditions of 40-60%, with a holding time of 3-10 minutes after each temperature increase.

9. The preparation method according to claim 3, characterized in that, In step (5), the hot pressing conditions are: temperature 80-120℃, pressure 5-15MPa, and processing time 2-8 minutes; the thickness of the polymer carbon nanotube composite conductive film obtained in step (5) is 50-150nm.

10. The application of the polymeric carbon nanotube composite conductive film according to claim 1 or 2, or the polymeric carbon nanotube composite conductive film prepared by the preparation method according to any one of claims 3 to 9, in antistatic packaging films, electromagnetic shielding films, flexible touch screens, electrochromic devices, organic light-emitting devices, solar cells, or heating films.